SEDIMENTOLOGICAL PROPERTIES OF THE 2010 MENTAWAI TSUNAMI DEPOSIT - Yudhicara Yudhicara; Andrian Ibrahim (Marine Geological Institute of Indonesia, 2012)
Post tsunami survey of the October 25, 2010, Mentawai tsunami, has been carried out by a collaboration team of Indonesian-German scientists from 20 to 28 November 2010. One activity of the researches were investigation on tsunami deposits along the coast following the event that devastated the islands of Sipora, North Pagai and South Pagai. Sedimentological properties of Mentawai tsunami deposit were explained by this study, from both megascopic and laboratory result. In general, beaches along the study area are underlying by a stretch of reef limestone, sediments mostly composed of white sand while grey sand was found only at Malakopa. Tsunami sediments were taken from 20 locations, start from Betumonga at Sipora Island until Sibaru-baru Island at the southern tip of the study area. The thickness of tsunami deposits are ranged between 1.5 and 22 cm, which are generally composed of fine to coarse sand in irregular boundaries with the underlying soil. Based on grain size analysis, variation of sedimentological properties of tsunami deposits range between phi=-0,5793 and phi=3,3180 or very coarse to very fine sand. Tsunami deposits mostly have multiple layers which described their transport processes, run up at the bottom and back wash at the top. Structural sediments such as graded bedding of fining upward, parallel lamination and soil clast were found. The grain size distribution curves show two types of mode peak, unimodal and multimodal which are indication of different sorting condition representing the source materials. While segment grain size accumulative plot generally shows domination of dilatation and traction transport mechanism rather than suspension. In general, very rare fossils were found from Mentawai tsunami deposit, but those findings gave information on how depth tsunami start to scour the seafloor and transport it landward, such as an abundance of Sponge spicule was found which indicate shallow water environments (20-100 m seafloor depth). Keywords: 2010 Mentawai tsunami, tsunami deposit, grain size analysis, fossils identification. Survei pasca-tsunami Mentawai 25 Oktober 2010, telah dilakukan oleh Tim gabungan Indonesia-Jerman pada tanggal 20 - 28 November 2010. Salah satunya adalah melakukan identifikasi endapan tsunami yang ditemukan di sepanjang pantai yang terlanda tsunami di Pulau Sipora, Pagai Utara dan Pagai Selatan. Berdasarkan hasil penelitian baik megaskopik maupun analisis laboratorium, dalam tulisan ini dapat dijelaskan mengenai sifat-sifat sedimentologi dari endapan tsunami Mentawai. Secara umum litologi penyusun pantai di daerah penelitian disusun oleh hamparan batugamping terumbu, sebagian disusun oleh pasir berwarna putih, sedangkan di Malakopa tersusun oleh endapan pasir pantai berwarna abu-abu. Berdasarkan hasil analisis laboratorium, diperoleh variasi sifat sedimentologi, seperti kisaran ukuran butir endapan tsunami antara -0,5793 phi dan 3,3180 phi, yaitu pasir sangat kasar hingga sangat halus. Endapan tsunami umumnya memiliki beberapa lapis yang menunjukkan adanya proses transportasi, seperti saat air naik (run up) di lapisan bagian bawah dan surut di bagian atas, yang ditunjukkan dengan adanya perbedaan ukuran butir. Struktur sedimen ditemukan seperti adanya perubahan besar butir secara berangsur menghalus ke bagian atas, perlapisan sejajar dan fragmen tanah yang terperangkap dalam sedimen. Kurva distribusi ukuran butir memperlihatkan dua jenis model puncak, yaitu unimodal dan multimodal yang memperlihatkan kondisi pemilahan yang berbeda yang menunjukkan kondisi sumber material endapan tsunami, sedangkan grafik akumulasi ukuran butir umumnya memperlihatkan dominasi mekanisme transportasi dilatasi dan traksi daripada suspensi. Secara umum fosil yang terkandung dalam endapan tsunami Mentawai sangat jarang, namun sedikit banyak telah memberikan informasi seberapa dalam gelombang tsunami mulai menggerus lantai samudera dan memindahkannya ke darat, misalnya dengan ditemukannya fosil bentonik Sponge spicule yang melimpah, menunjukkan asal lingkungan laut dangkal dengan kedalaman laut 20-100 m. Kata kunci: Tsunami Mentawai 2010, endapan tsunami, analisis besar butir, identifikasi fosil.